LAKI-LAKI DALAM PERKAWINAN NYEBURIN DI DESA KUKUH KECAMATAN MARGA KABUPATEN TABANAN - , PUTU SETYANINGRUM, Agus Sudaryanto, S.H.,M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research was to determine the causes of men carry out nyeburin marriage, responsibilities of sentana keceburin towards his household and the relatives of his wife, sanctions for the sentana keceburin if he does not carry out his responsibilities in Kukuh Village Tabanan Town. This research is a juridical sociological, because the primary data used as basic data obtained from field research and secondary data as supportive data obtained from study of literature. Field research data was conducted by interview, while literature data was done by documents study. The method of obtaining sample was done by purposive sampling method therefore research subjects consisted of four couples who married nyeburin, one parents from males couples, three parents from females couples, and five other reliable sources. The results obtained from the field and literature study was analyzed qualitatively and then transform into descriptive form. The results showed that there are three factors that causes men carry out nyeburin marriage, the first factor is because the strong emotion of love from men toward his spouse. Second factor, the women financially is wealthier than her spouse so it can improve the standard living of her spouse. Third factor is because there are too many sons in a family so the parent allows one of their sons to perform nyeburin marriage. Sentana Keceburin responsibilities to his household and his wifeâs relative are sekala responsibility such as maintaining physically and mentally of his wife and children and also provide the basic primer needs such as food, clothing and education. The other one is niskala responsibility such as conducting Panca Yadnya ceremonies which are consists of five types of sacred ceremony performed by Hindus to achieve perfection in life. No specific sanctions governing the nyeburin if the husband is not doing his duty. The sanctions provided for citizens in general if not doing their duty as citizens of the village customs not specifically indicated for nyeburin husband.